GOLGI TRANSPORT 1B Regulates Protein Export from the Endoplasmic Reticulum in Rice Endosperm Cells. Issue 11 (1st November 2016) - Wang, Yihua; Liu, Feng; Ren, Yulong; Wang, Yunlong; Liu, Xi; Long, Wuhua; Wang, Di; Zhu, Jianping; Zhu, Xiaopin; Jing, Ruonan; Wu, Mingming; Hao, Yuanyuan; et al.
Abstract : GOT1B regulates COPII-mediated protein export from the endoplasmic reticulum exit sites in developing rice endosperm cells. Abstract: Coat protein complex II (COPII) mediates the first step of anterograde transport of newly synthesized proteins from the endoplasmic reticulum (ER ) to other endomembrane compartments in eukaryotes. A group of evolutionarily conserved proteins (Sar1, Sec23, Sec24, Sec13, and Sec31) constitutes the basic COPII coat machinery; however, the details of how the COPII coat assembly is regulated remain unclear. Here, we report a protein transport mutant of rice ( Oryza sativa ), named glutelin precursor accumulation4 ( gpa4 ), which accumulates 57-kD glutelin precursors and forms two types of ER -derived abnormal structures. GPA4 encodes the evolutionarily conserved membrane protein GOT1B (also known as GLUP2), homologous to the Saccharomyces cerevisiae GOT1p. The rice GOT1B protein colocalizes with Arabidopsis thaliana Sar1b at Golgi-associated ER exit sites (ERESs) when they are coexpressed in Nicotiana benthamiana . Moreover, GOT1B physically interacts with rice Sec23, and both proteins are present in the same complex(es) with rice Sar1b. The distribution of rice Sar1 in the endomembrane system, its association with rice Sec23c, and the ERES organization pattern are significantly altered in the gpa4 mutant. Taken together, our results suggest that GOT1B plays an important role in mediating COPII vesicle formation at ERESs, thus facilitating anterograde transport of secretory proteins in plant cells.